Fatores associados ao parto cesariana no Hospital Universitário Cassiano Antonio Morais (HUCAM) - Rodrigues, Patrícia Leite (2016)
The cesarean birth rate has high values worldwide, setting the so-called epidemic of caesarean sections. The WHO recommends a rate of 10- 15% of deliveries performed by surgical means, considered safe for maternal and neonatal mortality, from which can exist increase in complications that doesn’t lead to improved quality of obstetric care. However, it is not the reality in most countries worldwide, including Brazil, which is one of the world champions where the majority of births occurring in this country is caesarean, reaching a rate of 56%. Among some determining factors for this reality, we can cite the clinical conditions, population, socioeconomic and cultural characteristics. This research proposes to assess the factors associate with cesarean section at the Hospital Universitário Cassiano Antonio Morais (HUCAM) in addition to studying the surgical birth rate, in order to elucidate critical issues in health care in this institution. The survey used the SIP database-CLAP from Projeto Mãe Adolescente at HUCAM involving the birth that occurred between April/2012 and December/2013, totalizing 2009 patients. The variables analysed were divided between maternal factors (maternal age, educations, previous pregnancy, c-section and BMI), obstretic factors (quality of pre-natal, gestacional age, diabetes and pre eclampsia) and neonatal factors (fetal presentation, APGAR, weight and IPR). Initially, was made a descriptive analysis of the data and adjustment for general linear models for the 3 groups of factors. The index of cesarean births was 58,8% and the factors associated with the surgical delivery were: cesarean section, maternal age over 20 years, diabetes and pre eclampsia, breech presentation, over than 41 weeks gestational age and weight of the newborn. We found a negative association with non caesarean sections and fetal size births, behaving as protective factors. At the end of this research, was made suggestions for action plans aiming improvements to this health service, in accordance with public policies to reduce the number of caesareans, like as: to maintan statistical service and to intensify fill the SIP CLAP, to promote continuing medical education and organizational changes in materials and health staff, the decentralization of education at the university hospital and the monitoring of the actions taken and the impact on the results found.